Truism of Sustainable Development Goals in Nigeria: Can Green Entrepreneurship serve as Catalyst? - Izevbigie, Iyen Don-Pedro (LPPM of NAROTAMA UNIVERSITY, 2025)
This study investigated the possible catalytic role of green entrepreneurship in Nigeria’s pursuit of the seventeen (17) United Nations Sustainable Development Goals (UN SDGs), with the UN haven set the year 2030 as its achievement’s deadline. Given an infinite population in focus in terms of environmental and sustainability practitioners in Nigeria, the Cochran 1977 sample size determination technique was used in arriving at a sample size of 384 respondents. However, for purpose of proactiveness, five hundred (500) copies of likert scale questionnaire were administered to environmental and sustainability practitioners in the government ministries, departments, and agencies, as well as industries, and academics. Three hundred and ninety-two (392) copies were however retrieved, and after sorting for defects, the sample size of 384 copies which conforms with Cochran (1977) sample size for infinite population were used for this study. The responses were coded, while SPSS 25 statistical and econometric software was used to run an undated ordinary least square (OLS) regression. The results of the analyses shows that green entrepreneurship has a significant negative relationship with SDGs in Nigeria. Based on this finding, it is recommended that government of Nigeria should set machinery in motion to ensure aggressive implementation of green entrepreneurship, particularly as the world approaches the 2030 deadline date set for the achievement of the 17 SDGs.